Nature-Based Solutions for Urban Sustainability: An Ecosystem Services Assessment of Plans for Singapore’s First “Forest Town” - Tan, Beverley Anne; Gaw, Leon Yan-Feng; Masoudi, Mahyar; Richards, Daniel Rex (Frontiers in Environmental Science, 2021)
Rapid urbanisation in many parts of the world has increasingly put the environment under pressure, with natural landscapes cleared to make way for built infrastructure. Urban ecosystems, and the services that they provide, can offer nature-based solutions to the challenges of urbanisation. There is increasing interest in better incorporating ecosystems into urban planning and design in order to deliver greater provision of ecosystem services and enhance urban liveability. However, there are few examples of built or proposed urban developments that have been designed specifically with ecosystem services in mind – partly because there are few modelling tools available to support urban planners and designers by informing their design workflows. Through using Singapore’s latest nature-centric town as a case study, this article assesses the impacts of nature-based solutions in urban design on ecosystem services performance, through a spatially-explicit modelling approach. The proposed future scenario for the nature-centric town was projected to result in substantial declines in the provision of all ecosystem services, as a result of the removal of large areas of natural vegetation cover. However, the future scenario compared favourably against three older towns that have been constructed in Singapore, showing the best performance for four out of six ecosystem services. This simulation exercise indicates that designing towns with ecosystem services in mind, and incorporating nature-based solutions into urban design, can help to achieve enhanced performance in providing ecosystem services. The models developed for this study have been made publicly available for use in other tropical cities.